2011
DOI: 10.1007/s11948-011-9276-0
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Many Hands: Climate Change as an Example

Abstract: In some situations in which undesirable collective effects occur, it is very hard, if not impossible, to hold any individual reasonably responsible. Such a situation may be referred to as the problem of many hands. In this paper we investigate how the problem of many hands can best be understood and why, and when, it exactly constitutes a problem. After analyzing climate change as an example, we propose to define the problem of many hands as the occurrence of a gap in the distribution of responsibility that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
106
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(117 citation statements)
references
References 36 publications
0
106
0
1
Order By: Relevance
“…Furthermore, they can interact with each other in unforeseeable ways and the actual use of any ICT technology or innovation often lies beyond the control of the innovator or researcher. This is caused, at least in part, by the "problem of many hands" [12,13]; the development of ICT, especially software, builds on past work which becomes embedded and can be impossible to extricate. It is therefore often impossible to draw causal chains from the actions of one person to a particular outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they can interact with each other in unforeseeable ways and the actual use of any ICT technology or innovation often lies beyond the control of the innovator or researcher. This is caused, at least in part, by the "problem of many hands" [12,13]; the development of ICT, especially software, builds on past work which becomes embedded and can be impossible to extricate. It is therefore often impossible to draw causal chains from the actions of one person to a particular outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Through use of existing ICT infrastructures, a researcher or innovator can devise new applications that have the potential to go viral and become available worldwide within an extremely short timescale. Secondly, the "problem of many hands" [42] stems from the issue that the development of ICTs is cumulative; new ICT developments often build upon and incorporate existing technologies. This is most visible in software where new code is built upon already existing codes.…”
Section: Ethical and Societal Risks Associated With Randi In Ictmentioning
confidence: 99%
“…In particular, we showed that it was unclear who was to be held accountable for Karnataka's biofuel policy, a result of both lobbying and policy-writing by researchers and the final policy proclamation by politicians. This situation can be characterised as a 'many hands problem' (Van de Poel et al 2012), where many parties are involved in a decision yet none of them can reasonably be held individually responsible for its consequences. Without a clear demarcation of responsibilities, one may also encounter accountability problems as it is not always clear who, if anyone, should be held accountable for particular problems (Balkema and Pols 2015;Setiawan and Singh 2015;Voeten et al 2014).…”
Section: Stakeholder Involvementmentioning
confidence: 99%